Kebijakan Publik Indonesia: Studi pada Kebijakan Pemerintah Tentang Pembatasan BBM Subsidi Tahun 2024 - Wahyu Trisno Aji; Mohammad Solekhan (STIKes Ibnu Sina Ajibarang, 2024)
This study examines the government's public policy related to the restriction of subsidized fuel oil (BBM) in 2024 through a public policy theory approach. This study uses a qualitative type with a case study with a literature study documentation data collection technique on the topic discussed. The results of the study Public policy is understood as government actions or inactions that reflect certain goals and values. In this context, the policy of restricting subsidized fuel was born as a response to public problems, especially the swelling of the state budget (APBN) due to energy subsidies. Through this policy, fuel subsidies are directed only to certain groups, such as public vehicles, transportation of basic goods, motorbikes under 150 cc, and cars with special criteria, which aim to make budget use more efficient. From the perspective of public policy theory, this step is included in the rational policy model, which seeks to prioritize the principle of